On the regularization of the spectral expansions of distributions with compact support - Rakhimov, Abdumalik (Federation of Engineering Institutions of Islamic Countries., 2016)
In this paper we study the summability of the spectral expansions of distributions from the Sobolev spaces with negative smoothness. The results obtained lead to the development of new interesting research directions of the spectral theory of differential operators. The results can be applied in the regularization of solutions of the problems in Engineering with applications of modern spectral methods of mathematical physics and computing systems in case when initial and/or boundary data of the problems presents some singularities and cannot be described by locally integrable functions.